'WE ONLY WANT TO PLANT OIL PALM": AN ETHNOHISTORY OF ILLEGAL PEASANT’S OIL PALM PLANTATIONS IN MUARO JAMBI, JAMBI PROVINCE, INDONESIA - Bachrioktora, Yudi (International Review of Humanities Studies, 2024)
The increasing global demand for vegetable oils and biofuels is a determining factor in increasing oil palm expansion in Indonesia. The current studies of Indonesia's oil palm expansion focus on companies' large-scale land acquisition. In this process, often called land grabbing, small peasants are excluded from the acceleration of oil palm expansion. This research focuses on the rarely discussed topic of the participation of small peasants in the palm oil production chain. Employing ethnohistory, this research unfolds the impact of oil palm expansion on small peasants and indigenous people, especially those who expand their plantations into the forest in Jambi Province. This research aims to show how peasants and indigenous peoples respond to the commercial crops boom in Indonesia.